Potential cardiotoxicity induced by Euodiae Fructus: In vivo and in vitro experiments and untargeted metabolomics research - Zhang, Dan; Lü, Jintao; Ren, Zhixin; Zhang, Xiaomeng; Wu, Huanzhang; Sa, Rina; Wang, Xiaofang; Wang, Yu; Lin, Zhijian; Zhang, Bing (Frontiers in Pharmacology, 2022)
Background: Euodiae Fructus, a well-known herbal medicine, has been widely used in Asia and has gained popularity in Western countries over the last decade. It has obvious side effects that have been observed in clinical settings, but few studies have reported on its cardiotoxicity. Methods: In the present study, the experiments in vivo and in vitro with the techniques of untargeted metabolomics were utilized to analyze the signaling mechanisms and endogenous metabolites of cardiotoxicity induced by Euodiae Fructus in H9c2, neonatal rat cardiomyocytes (NRCMs), and rats and to clarify the hazardous effects of Euodiae Fructus on cardiac function and metabolism from the point of overdose and unsuitable syndrome differentiation. Results: Cardiac cytotoxicity of evodiamine and rutaecarpine in vivo experiments was associated with remarkably alteration of LDH, CK, mitochondrial membrane potential, intensity of calcium fluorescence, the decreased protein expression of cGMP-PKG pathway in H9c2 cells and the frequency of spontaneous beat in NRCMs. Additionally, the results of rats with Yin deficiency suggested that there was obvious cardiac physiological function, abnormal ECG and pathological injury, decreased expression of PKG protein in high-dose group of Euodiae Fructus. At the level of endogenous metabolites, cardiac side effects of overdose and irrational usage of Euodiae Fructus was related to 34 differential metabolites and 10 metabolic pathways involving purine metabolism, glycerophospholipid metabolism, glycerolipid metabolism, sphingolipid metabolism, and so on. Conclusion: These findings shed new light on the cardiotoxicity induced by Euodiae Fructus which might be associated to overdose and unsuitable syndrome differentiation through modulating cGMP-PKG pathway and disturbing metabolic pathways of purine, lipid and amino acid. The continued research was necessary to facilitate the development of pharmacovigilance at providing scientific references to safe medication of Chinese herbs in the future.